Short-term exposure to ultrafine and fine particulate matter with multipollutant modelling on heart rate variability among seniors and children from the CorPuScula (coronary, pulmonary, sanguis) longitudinal study in Germany - Haddad, Pascale; Ogurtsova, Katherine; Lucht, Sarah; Glaubitz, Lina; Höppe, Peter; Nowak, Dennis; Angerer, Peter; Hoffmann, Barbara (Frontiers in Epidemiology, 2023)
Background: Short-term exposure particulate matter with a diameter of 10 µm or less (PM10) and fine particulate matter (PM2.5) has been associated with heart rate variability (HRV), but exposure to ultrafine particles (UFP) has been less well examined. We investigated the associations between the HRV outcomes and short-term exposure to UFP, PM10 and PM2.5 among children and seniors. Methods: CorPuScula (Coronary, Pulmonary and Sanguis) is a longitudinal, repeated-measure panel study conducted in 2000-2002 in Munich, Germany including 52 seniors (58 to 94 years old) with 899 observations and 50 children (6 to 10 years old) with 925 observations. A 10-minute resting electrocardiogram was performed to assess resting HRV outcomes (SDNN, RMSSD, LF, HF, LF/HF). UFP and PM exposures were measured near the care home and school yard for seniors and children, respectively. Mean exposures during the day of examination (9-21h) as well as 3-hour, 12-hour, 24-hour, one-day, and two-day lags were assessed. Linear mixed-effect models were used to investigate the associations between short-term air pollution and HRV outcomes separately in children and seniors adjusting for sex, age, weather conditions, BMI, lifestyle and medical information. Two and multipollutant models adjusted for NO2 and O3 were performed. Results: Among seniors, we observed increases in SDNN, LF, HF and LF/HF ratio after exposure to UFP (hourly and daily lags) in contrast to decreases in SDNN and RMSSD after exposure to PM10. Associations were robust to two- and multipollutant adjustment. Among children, we observed increases of the LF/HF ratio after exposures to UFP (lags 12 and 24 hours). In contrast, we observed decreases of the ratio after exposure to PM2.5 and PM10. Results were largely unchanged for multipollutant modelling, however we found a more pronounced increase in SDNN and LF/HF (UFP lag 12 and 24 hours) after adjusting for NO2. Conclusions: Overall, among seniors, we observed associations of UFP and PM10 exposure with sympathetic responses of the ANS, which play an important role in sudden heart attacks or arrhythmia. Among children we found more inconsistent associations between UFP and a delayed increase in HRV. Adjusting for co-pollutants including NO2 and O3 yielded robust results.